PENGARUH PENCITRAAN, KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA RUMAH MAKAN KAMPOENG DELI MEDAN - Nurafrina Siregar (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2017)
Imaging is one of the most important elements that should be owned by every agency of companies and institutions engaged in anything, in order to support the good name of the company which will be aimed at the development of the company. But it also should be the support of a quality product that imaging was not only as information that is not appropriate. So it must be the product that supports such imaging. And the price is a shared value of a product in accordance with the benefits of the product itself. Formulation of the problem in this study is whether imaging, product quality and price of the partial effect on customer loyaltyrestaurant Kampoeng Deli Medan. Do imaging, product quality and price simultaneous effect on customer loyalty restaurant Kampoeng Deli Medan. This study aimed to test whether the independent variables affect the dependent variable. The independent variable used in this research is imaging, product quality, and price and the dependent variable is customer loyalty. This research was conducted in the location of restaurants Kampoeng Deli Medan. The data used are primary data through questionnaires with respondents restaurant Kampoeng Deli Medan were 96 respondents. Data collected through questionnaires. The analytical methodused is descriptive quantitative method with the SPSS (Statistical Product and Service Solution). And tests conducted in this study is to test the quality of the data, the classic assumption test, and the test of determination that is based on the t value and significance values. From the results of simple linear analysis showed independent variables have a significant effect on the dependent. found that the significance of the image, product quality, and price above alpha 0.05 (5%), and t value X1 is equal to 503, X2 is equal to 2304 and X3 which for 1540 was greater than 1.661 (t> t table). Based on the hypothesis test results obtained it can be concluded that the independent variables namely imaging, product quality and price effect on customer loyalty.